2019
DOI: 10.1111/iej.13168
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of root canal treatment in teeth with preoperative apical periodontitis: a study with cone‐beam computed tomography and digital periapical radiography

Abstract: Aim This observational cohort study aimed: (i) to determine retrospectively after a 1‐ to 12‐year follow‐up period, the strength and independence of the association of various patient‐, tooth‐ and treatment‐related prognostic variables with the outcome of root canal treatment in patients with pre‐therapeutic apical periodontitis; and (ii) to establish the concordance between those predictors evaluated by both cone‐beam computed tomography (CBCT) and digital periapical radiography (DPR). Methodology The study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 49 publications
1
40
0
2
Order By: Relevance
“…When considering the long-term success of root canal treatment, coronal leakage may play an important role, perhaps as important as any aspect or step of the root canal treatment itself (Ray & Trope 1995). Unfortunately, the quality of coronal restorations, although considered relevant (Restrepo-Restrepo et al 2019), is difficult to assess on CBCT scans due to several types of image artefacts. Clinical examination and intraoral radiographs may be more reliable methods of evaluating the quality of coronal restorations (Tyndall & Rathore 2008) than CBCT imaging.…”
mentioning
confidence: 99%
“…When considering the long-term success of root canal treatment, coronal leakage may play an important role, perhaps as important as any aspect or step of the root canal treatment itself (Ray & Trope 1995). Unfortunately, the quality of coronal restorations, although considered relevant (Restrepo-Restrepo et al 2019), is difficult to assess on CBCT scans due to several types of image artefacts. Clinical examination and intraoral radiographs may be more reliable methods of evaluating the quality of coronal restorations (Tyndall & Rathore 2008) than CBCT imaging.…”
mentioning
confidence: 99%
“…Factors selected for such an evaluation may be more or less restrictive. In general terms, various studies base their analyses on one to three factors [ 3 , 12 , 13 , 14 , 15 , 16 , 17 ], while others assess the influence of multiple factors, taking into account preoperative, intraoperative, and postoperative factors [ 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The latter is the case of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Restrepo-Restrepo et al reported that irrigation with 2.5% sodium hypochlorite results in a decrease in the microhardness of the dentin. is is due to the ability of this irrigation agent to dissolve the organic component of the dentin, in particular, the collagen which adversely affects the quality of the sealer's adhesion and contributes to the decrease of the micromechanical interaction between the resin sealing cement and the dentin [4]. e humid state of the root canal at the obturation time has a very significant effect on the microleakage of the root canals filled with resincoated gutta-percha/EndoREZ ® , leading to a significant increase in the sealing performance [18,25].…”
Section: Discussionmentioning
confidence: 99%
“…ese materials must be biocompatible and nonresorbable, so that they can act as a dressing in the transition zone between the obturation and the periapical tissue [3,4].…”
Section: Introductionmentioning
confidence: 99%